2013
DOI: 10.1021/bi400708m
|View full text |Cite
|
Sign up to set email alerts
|

Fidelity, Mismatch Extension, and Proofreading Activity of the Plasmodium falciparum Apicoplast DNA Polymerase

Abstract: Plasmodium falciparum, a parasitic organism and one of the causative agents of malaria, contains an unusual organelle called the apicoplast. The apicoplast is a nonphotosynthetic plastid responsible for supplying the parasite with isoprenoid units and is therefore indispensable. Like mitochondria and the chloroplast, the apicoplast contains its own genome and harbors the enzymes responsible for its replication. In this report, we determine the relative probabilities of nucleotide misincorporation by the apicop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
46
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(48 citation statements)
references
References 28 publications
0
46
2
Order By: Relevance
“…1), which was referred to as KPom1 based on sequence similarity to the Klenow fragment of E. coli Pol I [24]. Most recently, the Nelson laboratory designed a construct based on sequence alignments (referred to as apPOL) and identified a possible polymerase boundary spanning residues 1389 to 2016 that is conserved across the Plasmodium genus [41,42] (Fig. 1).…”
Section: Polymerasementioning
confidence: 99%
See 3 more Smart Citations
“…1), which was referred to as KPom1 based on sequence similarity to the Klenow fragment of E. coli Pol I [24]. Most recently, the Nelson laboratory designed a construct based on sequence alignments (referred to as apPOL) and identified a possible polymerase boundary spanning residues 1389 to 2016 that is conserved across the Plasmodium genus [41,42] (Fig. 1).…”
Section: Polymerasementioning
confidence: 99%
“…The apPOL construct behaves more like the E. coli Klenow fragment, and its fidelity is reminiscent of other replicative DNA polymerases [41]. Differences in the reported fidelity of KPom1 and apPOL may not be solely due to the structural variances between the constructs, as the methods of analysis differed between the two proteins [41].…”
Section: Polymerasementioning
confidence: 99%
See 2 more Smart Citations
“…Following import, Prex is cleaved by an unknown protease into three separate proteins (Seow et al, 2005). The P. falciparum apicoplast DNA polymerase (apPOL) is the only known DNA polymerase targeted to the apicoplast, and we have previously demonstrated that the activity and fidelity of apPOL is consistent with that of a replicative DNA polymerase (Wingert et al, 2013).…”
Section: Introductionmentioning
confidence: 95%